Association of MDM4 Gene rs4245739 Polymorphism with the Risk and Clinical Characteristics of Colorectal Cancer in a Chinese Han Population - Zhao DM; Diao YE; Xu Q (Dove Medical Press, 2020)
De-Ming Zhao,1 Yu-E Diao,2 Qing Xu3 1Department of Gastrointestinal Surgery, Dalian Municipal Central Hospital, Dalian, People’s Republic of China; 2Department of General Surgery, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 3Department of Anorectal Surgery, Nantong Third People’s Hospital, Nantong University, Nantong, Jiangsu, People’s Republic of ChinaCorrespondence: Qing Xu Tel/Fax +86-513-89093902Email qing19xu@sina.comBackground: Studies show that MDM4 may play a pivotal role in colorectal cancer (CRC). Recently, a host of studies suggest that MDM4 gene rs4245739 polymorphism may modify the risk of different cancers.Methods: In this study, we were interested whether MDM4 gene rs4245739 polymorphism correlated with the risk and clinical characteristics of CRC. Logistic regression was adopted to estimate the association of rs4245739 polymorphism and CRC risk.Results: We enrolled 444 CRC patients and 530 controls and found MDM4 gene rs4245739 polymorphism may decrease the risk of CRC. Stratified analyses uncovered that this variant was connected to a less risk of CRC in females, non-drinkers, non-smokers, and people under 60 years old. Additionally, rs4245739 polymorphism was related to TNM staging, pathological type, tumor size, and location of CRC. Furthermore, this polymorphism was significantly linked with the survival of CRC.Conclusion: Totally, this study suggests that MDM4 rs4245739 polymorphism is linked with the risk and clinical characteristics of CRC.Keywords: MDM4, colorectal cancer, case–control study, rs4245739, polymorphism